Microeconomics Static and Dynamic Analysis - Malaga, Krzysztof; Sobczak, Karolina (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a comprehensive overview of the fundamental concepts and principles of microeconomics. It introduces students to the models, assumptions, and empirical applications of modern microeconomics, as well as to the necessary mathematical tools. It covers topics such as economic behavior, consumer theory, theory of the firm, partial and general equilibrium theory, industrial organization, bargaining theory, and Pareto optimality. Students learn not only about economic outcomes at a given point of equilibrium, but also about dynamic economics, which includes both equilibrium and disequilibrium. This book is intended for undergraduate and graduate students in economics and related fields who are interested in the basic theories and applications of microeconomics.
Chapter 1. Introduction -- Chapter 2. Rationality of choices made by individual consumer -- Chapter 3. Rationality of choices made by groups of consumers -- Chapter 4. Rationality of choices made by individual producers -- Chapter 5. Rationality of choices made by groups of producers by exogenously determined function of demand for product -- Chapter 6. Rationality of choices made by groups of producers and groups of consumers -- Chapter 7. Conclusion.
Keywords: Microeconomics; Econometrics; Microeconomics; Quantitative Economics